On the Temperature and Lubricant Film Thickness Distribution in EHL Contacts with Arbitrary Entrainment - Milan Omasta; Jakub Adam; Petr Sperka; Ivan Krupka; Martin Hartl (Lubricants, 2018)
An understanding of mechanisms which are responsible for elastohydrodynamic lubricant film formation under high sliding conditions is necessary to increase durability of machine parts. This work combines thin-film colorimetric interferometry for lubricant film thickness measurement and infrared microscopy for in-depth temperature mapping through the contact. The results describe the effect of operating conditions such as speed, slide-to-roll ratio, ambient temperature, and sliding direction on lubricant film thickness and temperature distribution. Film thickness data shows how much the film shape is sensitive to operating conditions when thermal effects are significant, while the temperature profiles provides an explanation of this behavior.